PENGGUNAAN DAN KEBIJAKAN MEDIA SOSIAL - Kosasi, Rindi; Nurmandi, Achmad; Misran , Misran (The Journal of Society and Media, 2024)
This research aims to study regulations on the use of social media around the world. This study uses a qualitative scientometric approach. The data source for this study was taken from the Scopus Database with the keywords "Social Media Use" and "Policies." There were 173 documents analyzed, and the data was filtered using bibliometrics based on keyword relevance, author country, and year of publication, which was limited to 2018-2022. Citespace software was used to process the data stored in RIS format. The study found that, firstly, 173 publications were addressing social media use and policy from 2018 to 2022. Second, the most published publications in the United States are 73; third, ten authors have collaborated in research on social media use and policy. The study also found that the social media use and policies of governments and countries worldwide continue to evolve as technology advances and people's behavior changes. Governments should make appropriate regulations and make good use of social media to communicate with the public and achieve their goals.